Electrolyte of high-safety sodium ion battery and secondary battery

By using an electrolyte containing specific solvents, film forming additives, conductive salts and additives in sodium ion batteries, the problem of gas production in sodium ion batteries is solved, and the safety and circulation stability of the battery are improved.

CN119542553APending Publication Date: 2025-02-28ANHUI JINHE SYNTHETIC MATERIAL RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964516.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Sodium ion batteries produce gas under high pressure conditions, causing increased internal pressure of the battery, which may cause expansion, leakage, short circuit and even fire of the battery, affecting the performance and safety of the battery.

Method used

A new sodium ion battery electrolyte is used, including propylene carbonate, vinyl carbonate, dimethyl carbonate as solvent, fluorovinyl carbonate and 1,3-propanesulfonolide as film forming additives, sodium perchlorate as conductive salt, and sodium acesulfonate and sodium nitrate as additives to improve the chemical stability and safety of the electrolyte.

Benefits of technology

The electrolyte reduces the oxidative decomposition of solvents and bubble generation under high pressure conditions, improves the conduction capacity of sodium ions, enhances the cycle stability and safety of the battery, controls the temperature rise of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218017740000151
    Figure BDA0005218017740000151
  • Figure BDA0005218017740000161
    Figure BDA0005218017740000161
Patent Text Reader

Abstract

The invention provides an electrolyte of a high-safety sodium ion battery, which comprises the following components: a solvent which takes propylene carbonate (PC) as a main solvent and contains ethylene carbonate (EC) and dimethyl carbonate (DMC); the coalescing agent is fluoroethylene carbonate (FEC) and 1, 3-propane sultone (1, 3-PS); conducting salt: sodium perchlorate (NaClO4); additives: acesulfame sodium and a proper amount of sodium nitrate. The sodium ion battery provided by the invention has more excellent properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy, in particular to electrolytes and secondary batteries. Background Art

[0002] Sodium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of sodium ions between the positive and negative electrodes to work, similar to the working principle of lithium-ion batteries. The charging and discharging process of sodium-ion batteries relies on the movement of sodium ions between the positive and negative electrodes. When charging, sodium ions are released from the positive electrode and embedded in the negative electrode through the electrolyte; when discharging, the opposite is true, sodium ions are released from the negative electrode and return to the positive electrode, while electrons move through the external circuit to form an electric current.

[0003] As a potential alternative to lithium-ion batteries, sodium-ion batteries (SIBs) have attracted widespread attention due to their abundant sodium resources, relatively low cost, and similar working principles to lithium-ion batteries. For sodium-ion batteries, gas production under high pressure directly threatens the overall safety of the battery system. During the battery charging and discharging process, especially under overcharge or high temperature conditions, a series of complex chemical reactions may occur inside the battery, leading to the generation and accumulation of gases (such as hydrogen, oxygen, etc.). The accumulation of these gases will rapidly increase the pressure inside the battery. If they cannot be released in a timely and effective manner, they will directly lead to the expansion or even rupture of the battery shell, causing serious consequences such as electrolyte leakage, short circuit, and even fire.

[0004] The performance and efficiency of sodium-ion batteries are key to their widespread application. Gassing under high pressure is often closely related to side reactions and parasitic reactions inside the battery. These unexpected reactions not only consume the active materials in the battery, reducing the amount of electricity available for normal charging and discharging, but may also lead to an increase in the internal resistance of the battery, thereby reducing the discharge capacity and cycle life of the battery. In addition, the tiny bubbles formed during the gassing process may hinder the effective transmission of ions in the electrolyte, further affecting the rate performance and power density of the battery. Therefore, high-pressure gassing not only impairs the immediate performance of the battery, but also seriously restricts its economy and reliability in long-term use.

[0005] In addition, the stability of electrode materials and electrolytes is the basis for maintaining efficient and stable operation of batteries. Under high-voltage conditions, the precipitation of gas in sodium-ion batteries is often accompanied by the destruction of the electrode structure and the decomposition of the electrolyte. For electrodes, the continuous generation of gas may cause the active substances to fall off and the pore structure to change, thereby affecting the conduction path of electrons and ions and reducing the reactivity of the electrodes. For electrolytes, the presence of gas may accelerate their chemical degradation, resulting in a decrease in ionic conductivity and even initiating interfacial reactions between the electrolyte and the electrode, forming byproducts that are not conducive to battery performance. These changes act together on the battery, resulting in a significant decrease in cycle performance and shortening the battery's service life.

[0006] The invention provides a new sodium ion battery electrolyte and a secondary battery with higher safety. Summary of the invention

[0007] The present invention provides an electrolyte for a sodium ion battery, the electrolyte comprising:

[0008] Solvent: Propylene carbonate (PC) as the main solvent, containing ethylene carbonate (EC) and dimethyl carbonate (DMC)

[0009] Film-forming aids: fluoroethylene carbonate (FEC) and 1,3-propane sultone (1,3-PS);

[0010] Conductive salt: sodium perchlorate (NaClO4);

[0011] Additives: acesulfame sodium and appropriate amount of sodium nitrate.

[0012] Furthermore, in the solvent, propylene carbonate (PC) accounts for 55-70% of the total mass of the solvent; ethylene carbonate (EC) accounts for 10-15% of the total mass of the solvent; and dimethyl carbonate (DMC) accounts for 10-15% of the total mass of the solvent.

[0013] Furthermore, in the film-forming aid, fluoroethylene carbonate (FEC) accounts for 5-10% of the total mass of the solvent; and 1,3-propane sultone (1,3-PS) accounts for 3-5% of the total mass of the solvent.

[0014] Furthermore, the conductive salt sodium perchlorate (NaClO4) accounts for 10%-25% of the total mass of the electrolyte.

[0015] Furthermore, the additive sodium acesulfame is 0.1%-2% of the total mass of the electrolyte.

[0016] Furthermore, the molar ratio of the sodium nitrate to acesulfame sodium is 1-1.5:2.

[0017] Further, it comprises the electrolyte according to any one of claims 1 to 6.

[0018] A sodium ion secondary battery, further comprising:

[0019] Positive electrode: It is formed by mixing sodium vanadium phosphate (NVP), conductive agent and binder in a certain proportion and then coating them on aluminum foil;

[0020] Negative electrode: formed by mixing hard carbon material, conductive agent and binder in a certain proportion and coating them on copper foil;

[0021] Diaphragm;

[0022] Battery case.

[0023] Furthermore, the active material in the positive electrode is sodium vanadium phosphate (NVP).

[0024] Furthermore, the active material in the negative electrode is a hard carbon material.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0026] The high-pressure resistance and good chemical stability of the electrolyte solvent ratio in the present invention help reduce the oxidative decomposition of the solvent under high pressure, thereby reducing the generation of bubbles; it provides an appropriate dielectric constant and viscosity, which helps the conduction of sodium ions and reduces unnecessary solvent decomposition reactions.

[0027] Highly efficient film-forming aids can not only effectively isolate the direct contact between the solvent and the electrode, reduce the solvent reduction or oxidation reaction, but also prevent the formation of bubbles and inhibit the oxidative decomposition of the electrolyte under high voltage.

[0028] The high stability and electrochemical window of the stable conductive salt help maintain the stability of the electrolyte and reduce the decomposition of the electrolyte and the generation of bubbles.

[0029] Additives improve the chemical stability of the electrolyte, reduce side reactions, and thus inhibit the generation of bubbles.

[0030] The electrolyte of the present invention performs better in controlling battery temperature rise and maintaining cycle stability. DETAILED DESCRIPTION

[0031] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0032] It is found in the prior art that sodium ion batteries will gradually generate gas during use. The first is the change in crystal structure. Under high voltage, layered oxide positive electrode materials may undergo complex phase changes. For example, when the bulk sodium ion content of P2-type or O3-type positive electrode materials is less than 1 / 3, the P-type structure will evolve to the O-type structure, which will cause a large volume change.

[0033] During high-voltage charge and discharge, the MO2 layer may slip, leading to structural rearrangement. This interlayer slip can cause changes in the coordination environment of sodium ions, such as the mutual transformation of octahedral sites and prismatic sites.

[0034] Under high voltage, the surface of the positive electrode material may degrade, such as the formation of cracks and the dissolution of transition metal ions, which will destroy the structural integrity of the material.

[0035] Structural changes can lead to changes in sodium storage performance. For example, the gas and byproducts produced under high voltage will occupy the internal space of the battery, reducing the sodium storage sites of the active material, resulting in a decrease in reversible capacity. Changes in crystal structure (such as phase transition and interlayer slip) will hinder the migration channel of sodium ions and reduce ion mobility.

[0036] Due to structural changes and surface degradation, the cycle stability of the positive electrode material will be affected, resulting in rapid performance degradation of the battery after multiple charge and discharge cycles.

[0037] The changes in battery performance are mainly reflected in three aspects: decreased energy density, increased internal resistance, and safety issues. The reduction in reversible capacity directly leads to a decrease in the battery's energy density, affecting the battery's overall endurance. Changes in crystal structure and the generation of byproducts will increase the battery's internal resistance, reducing the battery's output power and efficiency. The generation and accumulation of internal gas may cause safety issues such as battery expansion, leakage, and even explosion.

[0038] The invention provides a sodium ion battery electrolyte and a sodium ion secondary battery with high safety.

[0039] The electrolyte composition of the present invention is as follows:

[0040] Solvent: Propylene carbonate (PC) is the main solvent, and its mass is 55-70% of the solvent mass. At the same time, ethylene carbonate (EC) and dimethyl carbonate (DMC) are added as co-solvents to balance the viscosity, conductivity and electrochemical window of the electrolyte; ethylene carbonate (EC) is 10-15% of the solvent mass, and dimethyl carbonate (DMC) is 10-15% of the solvent mass. Fluorinated ethylene carbonate (FEC) and 1,3-propane sultone (1,3-PS) are also added as film-forming aids, and FEC is 5-10% of the solvent mass fraction. FEC can form a high-quality SEI film on the electrode surface, protect the electrode material from the erosion of the electrolyte, and at the same time widen the electrochemical window of the electrolyte and improve the high-voltage stability of the battery. The mass fraction of 1,3-PS in the solvent is 3-5%. 1,3-PS can participate in the formation of the solid electrolyte interface (SEI), improve the stability and mechanical strength of SEI, and thus enhance the cycle stability of the battery.

[0041] Conductive salt: Sodium perchlorate (NaClO4) is selected as the conductive salt, and its mass fraction is 10%-25% of the total mass of the electrolyte.

[0042] additive:

[0043] Sodium acesulfame: As another additive, its addition amount is 0.1%-2% of the total mass of the electrolyte. Sodium acesulfame can improve the interface properties of the electrolyte and enhance battery performance.

[0044] Nitrate ion (NO3-): As an anion additive with a high DN value, its addition amount should be appropriate. Nitrate ion can enhance the coordination effect between anion and Na+, weaken the interaction between solvent and Na+, thereby promoting the desolvation process of Na+ and improving the ionic conductivity of the electrolyte. The molar ratio of its addition to the molar amount of acesulfame sodium is 1-1.5:2.

[0045] Electrolyte preparation method:

[0046] The raw materials are as follows: Propylene carbonate (PC), PC has high chemical stability and high voltage resistance, and is one of the important solvents in sodium ion battery electrolyte. Ethylene carbonate (EC), EC has a high dielectric constant, which helps dissolve sodium salts, but has a high viscosity and needs to be mixed with other solvents. Dimethyl carbonate (DMC), DMC has low viscosity and can reduce the viscosity of the electrolyte and improve the ion transmission efficiency. Sodium perchlorate (NaClO4), NaClO4 is a commonly used sodium salt with high ionic conductivity and chemical stability. 1,3-Propane sultone (1,3-PS), 1,3-PS as an additive can improve the electrochemical window of the electrolyte and improve the cycle stability of the battery. Fluorinated ethylene carbonate (FEC), FEC can participate in the formation of a stable solid electrolyte interface (SEI) and reduce the decomposition of the electrolyte. Sodium acesulfame (ASNA), ASNA as another additive can further improve the performance of the electrolyte and improve the safety of the battery.

[0047] Raw material handling:

[0048] All solvents (PC, EC, DMC) are dried to ensure that the moisture content is below the specified standard. Moisture is a harmful substance in the electrolyte and will react with sodium salt to form impurities, reducing the purity and performance of the electrolyte. Drying is carried out by molecular sieves, vacuum drying or heating reflux.

[0049] For solid raw materials such as NaClO4, 1,3-PS, FEC and ASNA, grinding and sieving are carried out according to the raw material conditions to ensure uniform particle size and facilitate dissolution. At the same time, these raw materials also need to be stored in a dry and dark environment to avoid moisture absorption and decomposition.

[0050] Electrolyte preparation steps

[0051] Solvent mixing: In a protective gas atmosphere (such as argon or nitrogen), mix PC, EC and DMC in a predetermined ratio. The mixing process must be carried out under water-free and oxygen-free conditions to avoid the reaction of the solvent with oxygen and moisture in the air. The mixing ratio of PC, EC and DMC is between 2:3:5 and 1:1:1.

[0052] Sodium salt dissolution: Add an appropriate amount of NaClO4 to the uniformly mixed solvent and stir until completely dissolved. The solubility of NaClO4 is greatly affected by temperature and it is usually soluble at room temperature. However, in order to speed up the dissolution rate and improve the solubility, the solution can be heated to 40-50°C. During the stirring process, the stirring speed and stirring time must be controlled to ensure that the NaClO4 is completely dissolved and no solid particles remain.

[0053] Additive addition: Add additives such as 1,3-PS, FEC and ASNA in sequence, and continue stirring until all additives are completely dissolved. The order of adding additives and the stirring conditions need to be adjusted according to the properties of the additives. 1,3-PS and FEC have strong reducing properties and need to be added under anaerobic conditions and avoid contact with metals. The solubility of ASNA may be slightly poor, so the stirring time needs to be appropriately extended or the solution needs to be heated to promote its dissolution.

[0054] Filtration: Use a filter membrane to filter the prepared electrolyte to remove solid particles and impurities. During the filtration process, it is necessary to select a suitable filter membrane pore size and material to ensure the purity and stability of the electrolyte. The filtration operation must also be carried out under water-free and oxygen-free conditions to avoid contact between the electrolyte and oxygen and moisture in the air.

[0055] Storage and protection: Store the filtered electrolyte in a dry, light-proof, sealed container to avoid contact with air and moisture. The storage environment must maintain a constant temperature and humidity to avoid the effects of temperature fluctuations and excessive humidity on the electrolyte.

[0056] PC, EC and DMC, as solvents for sodium-ion battery electrolytes, each have unique properties. PC has high chemical stability and high voltage resistance, but has a high viscosity; EC has a high dielectric constant, which helps dissolve sodium salts, but also has a high viscosity; DMC has a low viscosity, which can reduce the viscosity of the electrolyte and improve the ion transmission efficiency. Therefore, mixing these three solvents in a certain proportion can give full play to their respective advantages and improve the overall performance of the electrolyte.

[0057] The solvent mixing process must follow the principle of like dissolves like, that is, solvents with similar polarity are more likely to dissolve in each other. PC, EC and DMC are all polar solvents with good mutual solubility. At the same time, the stirring speed and stirring time must be controlled during the mixing process to ensure that the solvents are mixed evenly without stratification.

[0058] For the dissolution and ionic conductivity of sodium salts:

[0059] As the sodium salt of sodium ion battery electrolyte, the solubility and ionic conductivity of NaClO4 have an important influence on the performance of the electrolyte. Solubility is affected by factors such as solvent properties, temperature and stirring conditions. Under appropriate conditions, NaClO4 can be completely dissolved in the solvent to form a uniform electrolyte. Ionic conductivity is related to factors such as the dielectric constant and viscosity of the solvent and the solvation structure of sodium ions. By optimizing the solvent composition and the type of additives, the ionic conductivity of the electrolyte can be improved and the internal resistance of the battery can be reduced.

[0060] Additives such as 1,3-PS, FEC and ASNA play an important role in the electrolyte. 1,3-PS can improve the electrochemical window of the electrolyte and improve the cycle stability of the battery. Its mechanism of action is mainly to preferentially undergo oxidation or reduction reactions on the electrode surface during the charge and discharge process to form a stable solid electrolyte interface (CEI) or SEI film, which prevents solvent molecules from directly contacting the electrode and reduces the decomposition of the electrolyte. FEC also has a similar mechanism of action and can participate in the formation of a stable SEI film. ASNA mainly improves the safety of the battery by improving the chemical stability and thermal stability of the electrolyte.

[0061] Method for manufacturing a sodium ion secondary battery.

[0062] Positive electrode preparation: Sodium vanadium phosphate (NVP), conductive agent and binder are mixed evenly in a certain proportion, an appropriate amount of solvent is added to form a slurry, which is coated on aluminum foil to form a positive electrode sheet, and then cut into the required size after drying.

[0063] Negative electrode preparation: Mix the hard carbon material, conductive agent and binder evenly, apply them on copper foil to form a negative electrode sheet, and cut it into the required size after drying.

[0064] Diaphragm selection: Choose polyolefin composite diaphragm as the diaphragm material.

[0065] Battery assembly: Use the aluminum-plastic film specially used for soft-pack batteries as the battery shell, wind the positive electrode sheet, negative electrode sheet and separator to form a battery core, put it into the aluminum-plastic film, inject the above-prepared electrolyte, and then heat-seal the aluminum-plastic film to ensure the sealing of the battery.

[0066] According to the technical solution of the present invention, 15 embodiments have been completed, which are as follows:

[0067] Example 1

[0068] Electrolyte composition:

[0069] Solvent: propylene carbonate (PC) 60%, ethylene carbonate (EC) 12%, dimethyl carbonate (DMC) 13%, fluoroethylene carbonate (FEC) 9%, 1,3-propane sultone (1,3-PS) 4%

[0070] Conductive salt: Sodium perchlorate (NaClO4) 20%

[0071] Additives: 1% acesulfame sodium, appropriate amount of nitrate ion (NO3-) (the molar ratio with acesulfame sodium is 1.25:2)

[0072] Sodium-ion secondary battery manufacturing:

[0073] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0074] Negative electrode: hard carbon material as active material

[0075] Diaphragm: Polyolefin composite diaphragm

[0076] Battery shell: Aluminum-plastic film for soft-pack batteries

[0077] Example 2

[0078] Electrolyte composition:

[0079] Solvent: Propylene carbonate (PC) 57%, Ethylene carbonate (EC) 14%, Dimethyl carbonate (DMC) 14%, Fluorinated ethylene carbonate (FEC) 8%, 1,3-propane sultone (1,3-PS) 3%

[0080] Conductive salt: Sodium perchlorate (NaClO4) 18%

[0081] Additives: 0.5% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1:2)

[0082] Sodium-ion secondary battery manufacturing:

[0083] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0084] Negative electrode: hard carbon material as active material

[0085] Diaphragm: Polyolefin composite diaphragm

[0086] Battery shell: Aluminum-plastic film for soft-pack batteries

[0087] Example 3

[0088] Electrolyte composition:

[0089] Solvent: propylene carbonate (PC) 65%, ethylene carbonate (EC) 11%, dimethyl carbonate (DMC) 11%, fluoroethylene carbonate (FEC) 7%, 1,3-propane sultone (1,3-PS) 5%

[0090] Conductive salt: Sodium perchlorate (NaClO4) 22%

[0091] Additives: 1.5% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1.3:2)

[0092] Sodium-ion secondary battery manufacturing:

[0093] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0094] Negative electrode: hard carbon material as active material

[0095] Diaphragm: Polyolefin composite diaphragm

[0096] Battery shell: Aluminum-plastic film for soft-pack batteries

[0097] Example 4

[0098] Electrolyte composition:

[0099] Solvent: propylene carbonate (PC) 55%, ethylene carbonate (EC) 15%, dimethyl carbonate (DMC) 15%, fluoroethylene carbonate (FEC) 10%, 1,3-propane sultone (1,3-PS) 3%

[0100] Conductive salt: Sodium perchlorate (NaClO4) 16%

[0101] Additives: 2% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1.5:2)

[0102] Sodium-ion secondary battery manufacturing:

[0103] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0104] Negative electrode: hard carbon material as active material

[0105] Diaphragm: Polyolefin composite diaphragm

[0106] Battery shell: Aluminum-plastic film for soft-pack batteries

[0107] Example 5

[0108] Electrolyte composition:

[0109] Solvent: propylene carbonate (PC) 70%, ethylene carbonate (EC) 10%, dimethyl carbonate (DMC) 10%, fluoroethylene carbonate (FEC) 5%, 1,3-propane sultone (1,3-PS) 5%

[0110] Conductive salt: Sodium perchlorate (NaClO4) 10%

[0111] Additives: 0.1% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1:2)

[0112] Sodium-ion secondary battery manufacturing:

[0113] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0114] Negative electrode: hard carbon material as active material

[0115] Diaphragm: Polyolefin composite diaphragm

[0116] Battery shell: Aluminum-plastic film for soft-pack batteries

[0117] Example 6

[0118] Electrolyte composition:

[0119] Solvent: Propylene carbonate (PC) 58%, Ethylene carbonate (EC) 13%, Dimethyl carbonate (DMC) 14%, Fluorinated ethylene carbonate (FEC) 6%, 1,3-propane sultone (1,3-PS) 4%

[0120] Conductive salt: Sodium perchlorate (NaClO4) 24%

[0121] Additives: 0.8% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1.1:2)

[0122] Sodium-ion secondary battery manufacturing:

[0123] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0124] Negative electrode: hard carbon material as active material

[0125] Diaphragm: Polyolefin composite diaphragm

[0126] Battery shell: Aluminum-plastic film for soft-pack batteries

[0127] Example 7

[0128] Electrolyte composition:

[0129] Solvent: propylene carbonate (PC) 62%, ethylene carbonate (EC) 12%, dimethyl carbonate (DMC) 12%, fluoroethylene carbonate (FEC) 8%, 1,3-propane sultone (1,3-PS) 4%

[0130] Conductive salt: Sodium perchlorate (NaClO4) 25%

[0131] Additives: 1% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1.2:2)

[0132] Sodium-ion secondary battery manufacturing:

[0133] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0134] Negative electrode: hard carbon material as active material

[0135] Diaphragm: Polyolefin composite diaphragm

[0136] Battery shell: Aluminum-plastic film for soft-pack batteries

[0137] Example 8

[0138] Electrolyte composition:

[0139] Solvent: Propylene carbonate (PC) 56%, Ethylene carbonate (EC) 15%, Dimethyl carbonate (DMC) 14%, Fluorinated ethylene carbonate (FEC) 10%, 1,3-propane sultone (1,3-PS) 3%

[0140] Conductive salt: Sodium perchlorate (NaClO4) 12%

[0141] Additives: 1.8% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1.4:2)

[0142] Sodium-ion secondary battery manufacturing:

[0143] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0144] Negative electrode: hard carbon material as active material

[0145] Diaphragm: Polyolefin composite diaphragm

[0146] Battery shell: Aluminum-plastic film for soft-pack batteries

[0147] Example 9

[0148] Electrolyte composition:

[0149] Solvent: propylene carbonate (PC) 67%, ethylene carbonate (EC) 11%, dimethyl carbonate (DMC) 11%, fluoroethylene carbonate (FEC) 6%, 1,3-propane sultone (1,3-PS) 3%

[0150] Conductive salt: Sodium perchlorate (NaClO4) 19%

[0151] Additives: 0.3% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1:1.5)

[0152] Sodium-ion secondary battery manufacturing:

[0153] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0154] Negative electrode: hard carbon material as active material

[0155] Diaphragm: Polyolefin composite diaphragm

[0156] Battery shell: Aluminum-plastic film for soft-pack batteries

[0157] Example 10

[0158] Electrolyte composition:

[0159] Solvent: propylene carbonate (PC) 59%, ethylene carbonate (EC) 14%, dimethyl carbonate (DMC) 12%, fluoroethylene carbonate (FEC) 7%, 1,3-propane sultone (1,3-PS) 5%

[0160] Conductive salt: Sodium perchlorate (NaClO4) 14%

[0161] Additives: 1.2% sodium acesulfame, appropriate amount of nitrate ion (NO3-) (the molar ratio with sodium acesulfame is 1.2:2)

[0162] Sodium-ion secondary battery manufacturing:

[0163] Positive electrode: sodium vanadium phosphate (NVP) as active material

[0164] Negative electrode: hard carbon material as active material

[0165] Diaphragm: Polyolefin composite diaphragm

[0166] Battery shell: Aluminum-plastic film for soft-pack batteries

[0167] Embodiment 11

[0168] Electrolyte composition:

[0169] Solvent: Propylene carbonate (PC) 65%

[0170] Ethylene carbonate (EC) 10%

[0171] Dimethyl carbonate (DMC) 15%

[0172] Fluoroethylene carbonate (FEC) 5%

[0173] 1,3-Propane sultone (1,3-PS) 3%

[0174] Conductive salt: Sodium perchlorate (NaClO4) 22%

[0175] Additive: Acesulfame Sodium 1.5%

[0176] The molar ratio of nitrate ion (NO3-) to acesulfame sodium is 1.3:2

[0177] Sodium ion secondary battery manufacturing: same as Example 1

[0178] Example 12

[0179] Electrolyte composition:

[0180] Solvent: Propylene carbonate (PC) 70%

[0181] Ethylene carbonate (EC) 15%

[0182] Dimethyl carbonate (DMC) 10%

[0183] Fluoroethylene carbonate (FEC) 3%

[0184] 1,3-Propane sultone (1,3-PS) 4%

[0185] Conductive salt: Sodium perchlorate (NaClO4) 15%

[0186] Additive: Acesulfame Sodium 2%

[0187] The molar ratio of nitrate ion (NO3-) to acesulfame sodium is 1.5:2

[0188] Sodium ion secondary battery manufacturing: same as Example 1

[0189] Embodiment 13

[0190] Electrolyte composition:

[0191] Solvent: Propylene carbonate (PC) 58%

[0192] Ethylene carbonate (EC) 14%

[0193] Dimethyl carbonate (DMC) 13%

[0194] Fluoroethylene carbonate (FEC) 9%

[0195] 1,3-Propane sultone (1,3-PS) 3%

[0196] Conductive salt: Sodium perchlorate (NaClO4) 20%

[0197] Additive: Acesulfame Sodium 0.7%

[0198] The molar ratio of nitrate ion (NO3-) to acesulfame sodium is 1.1:2

[0199] Sodium ion secondary battery manufacturing: same as Example 1

[0200] Embodiment 14

[0201] Electrolyte composition:

[0202] Solvent: Propylene carbonate (PC) 62%

[0203] Ethylene carbonate (EC) 11%

[0204] Dimethyl carbonate (DMC) 12%

[0205] Fluoroethylene carbonate (FEC) 8%

[0206] 1,3-Propane sultone (1,3-PS) 5%

[0207] Conductive salt: Sodium perchlorate (NaClO4) 18%

[0208] Additive: Acesulfame Sodium 0.3%

[0209] The molar ratio of nitrate ion (NO3-) to acesulfame sodium is 1:2

[0210] Sodium ion secondary battery manufacturing: same as Example 1

[0211] Embodiment 15

[0212] Electrolyte composition:

[0213] Solvent: Propylene carbonate (PC) 57%

[0214] Ethylene carbonate (EC) 13%

[0215] Dimethyl carbonate (DMC) 15%

[0216] Fluoroethylene carbonate (FEC) 10%

[0217] 1,3-Propane sultone (1,3-PS) 3%

[0218] Conductive salt: Sodium perchlorate (NaClO4) 22%

[0219] Additive: Acesulfame Sodium 0.1%

[0220] The molar ratio of nitrate ion (NO3-) to acesulfame sodium is 1.4:2

[0221] Sodium ion secondary battery manufacturing: same as Example 1.

[0222] For the above embodiments, in order to test the corresponding performance, the following tests were performed:

[0223] Constant current charge and discharge test: Through constant current charge and discharge test, the reversible capacity, cycle stability and rate performance of the battery are evaluated; as well as pulse charge and discharge test.

[0224] The constant voltage charging test equipment and method are as follows:

[0225] Test equipment: Charge and discharge tester: used to provide a constant charging voltage and record parameters such as current, voltage and time during the charging process. Data acquisition system: used to collect and store test data in real time.

[0226] Test method:

[0227] Place the battery in the test equipment and connect the positive and negative electrodes and the temperature sensor.

[0228] Set the constant voltage charging voltage, this time choose 4.4V.

[0229] Start charging and record the current change, charging time and battery temperature during the charging process.

[0230] When the charging current drops to the set threshold 0.01C (C is the rated capacity of the battery), charging is considered to be completed.

[0231] Record the charge capacity and safety at the end of charging.

[0232] Test results and analysis:

[0233]

[0234]

[0235] Next, the battery is subjected to pulse charge and discharge tests.

[0236] The specific steps of the test method are as follows:

[0237] The sodium ion secondary battery to be tested is fully charged under standard charging conditions and left to stand for a period of time (eg, 2 hours) to ensure that the internal state of the battery is stable.

[0238] Connect the battery to the pulse charge and discharge test equipment to ensure that the battery can correctly receive and respond to the charge and discharge instructions issued by the test equipment.

[0239] Set the test parameters, including the pulse charge and discharge current, duration, pulse interval, and total number of test cycles.

[0240] According to the preset parameters, start the pulse charge and discharge test.

[0241] After each charge and discharge pulse, the battery's voltage response, charge and discharge time, and charge and discharge amount are recorded.

[0242] Test conditions:

[0243] Charging pulse: The current density is 1C (i.e. the current corresponding to the rated capacity of the battery), and the duration is 5 minutes.

[0244] Discharge pulse: The current density is 2C, and the duration is determined by the battery capacity and the required discharge depth to ensure that a certain proportion of the battery power remains after the discharge is completed for the next charging pulse.

[0245] Pulse interval: In order to fully restore the internal state of the battery, a rest time of about 5 minutes should be set between each charge and discharge pulse.

[0246] Ambient temperature: The test environment temperature was controlled at 25±2℃ to reduce the impact of temperature on battery performance.

[0247] Test times: Perform at least 500 pulse charge and discharge cycles to evaluate the cycle stability of the battery.

[0248] In the test results:

[0249] The capacity recovery rate measures the degree of battery capacity recovery after pulse charge and discharge. The higher the value, the more stable the battery performance.

[0250] Cycle stability is tested through multiple pulse charge and discharge tests to observe the attenuation of battery performance and evaluate the long-term performance of the battery.

[0251] These values ​​indirectly reflect the internal performance of the battery.

[0252] Example Capacity recovery rate Cycle stability (capacity decay after 500 cycles) 1 ≥95% ≤5% 2 ≥94% ≤6% 3 ≥96% ≤4% 4 ≥97% ≤3% 5 ≥93% ≤7% 6 ≥94% ≤5% 7 ≥96% ≤4% 8 ≥97% ≤3% 9 ≥93% ≤6% 10 ≥95% ≤5% 11 ≥96% ≤4% 12 ≥93% ≤5% 13 ≥95% ≤5% 14 ≥93% ≤4% 15 ≥92% ≤6%

[0253] In the present invention, the constant voltage charging test results show that the batteries of Examples 1-15 exhibit excellent charging performance, charging capacity, safety and good battery temperature control under 4.4V constant voltage charging conditions.

[0254] Specifically, the charging time of each embodiment is kept within a narrow range, that is, between 2.3-2.8 hours, and the charging capacity is close to the rated capacity of the battery, which fully demonstrates the excellent technical effect of the electrolyte. In terms of safety, all embodiments exceed the high level of 92%, and some embodiments such as embodiments 3, 6, 7, and 11 reach more than 96%, among which embodiment 6 is as high as 97%. This significantly reflects the important role of electrolyte composition in improving safety. At the same time, the battery temperature changes of each embodiment are controlled within 13°C, and the battery temperature rise of embodiments 3, 6, and 7 is controlled at 9°C or below, showing better temperature control performance.

[0255] In the pulse charge and discharge test, the batteries of Examples 1-15 also exhibited excellent performance.

[0256] In terms of capacity recovery rate, all embodiments showed a relatively high level, exceeding 93%, and some embodiments such as embodiments 4 and 8 even reached more than 97%. This result once again proves the significant effect of electrolyte composition on capacity recovery rate.

[0257] Cycling stability is a key indicator for evaluating the long-term performance of batteries. In the present invention, after 500 cycles, the capacity decay of each embodiment is controlled within 7%, especially in embodiments 3, 4, 7, and 8, the capacity decay is as low as close to or less than 4%, showing the good influence of electrolyte composition on cycling stability.

[0258] During the charge and discharge process of the battery, the loss of active materials, changes in the crystal structure or the generation of by-products may lead to a decrease in the reversible capacity. These changes will occupy the internal space of the battery, reduce the sodium storage sites of the active materials, and thus affect the energy storage capacity of the battery. From the test results of the embodiment, although the capacity recovery rate and cycle stability of each battery are good, long-term charge and discharge cycles may still lead to a gradual decrease in the reversible capacity.

[0259] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A highly safe sodium ion battery electrolyte, characterized in that: The electrolyte includes: Solvent: Propylene carbonate (PC) as the main solvent, containing ethylene carbonate (EC) and dimethyl carbonate (DMC) Film-forming aids: fluoroethylene carbonate (FEC) and 1,3-propane sultone (1,3-PS); Conductive salt: sodium perchlorate (NaClO4); Additives: acesulfame sodium and appropriate amount of sodium nitrate.

2. The electrolyte according to claim 1, characterized in that In the solvent, propylene carbonate (PC) accounts for 55-70% of the total mass of the solvent; ethylene carbonate (EC) accounts for 10-15% of the total mass of the solvent; and dimethyl carbonate (DMC) accounts for 10-15% of the total mass of the solvent.

3. The electrolyte according to claim 1, characterized in that In the film-forming aid, fluoroethylene carbonate (FEC) accounts for 5-10% of the total mass of the solvent; and 1,3-propane sultone (1,3-PS) accounts for 3-5% of the total mass of the solvent.

4. The electrolyte according to claim 1, characterized in that The conductive salt sodium perchlorate (NaClO4) accounts for 10%-25% of the total mass of the electrolyte.

5. The electrolyte according to claim 1, characterized in that The additive sodium acesulfame is 0.1%-2% of the total mass of the electrolyte.

6. The electrolyte according to claim 1, characterized in that The molar ratio of the sodium nitrate to acesulfame sodium is 1-1.5:

2.

7. A sodium ion secondary battery, characterized in that: Comprising the electrolyte according to any one of claims 1 to 6.

8. The sodium ion secondary battery according to claim 7, characterized in that: Also includes: Positive electrode: It is formed by mixing sodium vanadium phosphate (NVP), conductive agent and binder in a certain proportion and then coating them on aluminum foil; Negative electrode: formed by mixing hard carbon material, conductive agent and binder in a certain proportion and coating them on copper foil; Diaphragm; Battery case.

9. The sodium ion secondary battery according to claim 7, characterized in that: The active material in the positive electrode is sodium vanadium phosphate (NVP).

10. The sodium ion secondary battery according to claim 7, characterized in that: The active material in the negative electrode is a hard carbon material.